Chapter Können Tiere irren? Philosophische Antworten aus dem 13. und 14. Jahrhundert - Oelze, Anselm (Miscellanea Mediaevalia, 2018)
The volume is a comprehensive evaluation of epistemic, practical, veridical issues from the perspective of every kind of failure, disruption, or confusion that comes under the general rubric of "error." The analysis is not limited to the element of negativity, but rather, an inquiry about the extent that error can be transformed into a starting point or precondition for successful epistemic practices.